Strategic analysis of tourism in the amazon: ecotourism and its potential for development - Neves Bulbol of Lima, Angela (Seven Editora, 2023)
The present work has as its theme the Strategic Analysis of Tourism in the Amazon: Ecotourism and its Potential for Differentiation in the process of strategic planning in tourism. The objective is to strategically analyze tourism in the Amazon, making use of all the potential of ecotourism for the differentiation and competitiveness of the State. DOI: https://doi.org/10.56238/tfisdwv1-084